2014
DOI: 10.1002/we.1812
|View full text |Cite
|
Sign up to set email alerts
|

Simplified critical mudline bending moment spectra of offshore wind turbine support structures

Abstract: Offshore wind turbines are subjected to multiple dynamic loads arising from the wind, waves, rotational frequency (1P) and blade passing frequency (3P) loads. In the literature, these loads are often represented using a frequency plot where the power spectral densities (PSDs) of wave height and wind turbulence are plotted against the corresponding frequency range. The PSD magnitudes are usually normalized to unity, probably because they have different units, and thus, the magnitudes are not directly comparable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
54
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(58 citation statements)
references
References 37 publications
2
54
0
2
Order By: Relevance
“…In summary, scour has been shown to influence the fatigue life (FL) of OWTs, and the effect of scour and backfilling on long‐term damage in a parked wind turbine has been researched . Due to the complexities associated with the fatigue analysis of OWTs, simplified methods have been proposed for this analysis . However, the quantification of the scour influence on the FL of an operational wind turbine and specific simplified methods for scour effects on fatigue analysis remain outstanding.…”
Section: Introductionsupporting
confidence: 82%
“…In summary, scour has been shown to influence the fatigue life (FL) of OWTs, and the effect of scour and backfilling on long‐term damage in a parked wind turbine has been researched . Due to the complexities associated with the fatigue analysis of OWTs, simplified methods have been proposed for this analysis . However, the quantification of the scour influence on the FL of an operational wind turbine and specific simplified methods for scour effects on fatigue analysis remain outstanding.…”
Section: Introductionsupporting
confidence: 82%
“…Typical wave period will be in the order of 10sec (for North Sea) and will therefore have dynamic soil-structure interaction. A calculation procedure is developed in Arany et al [6] and the output of such a calculation will be relative wind and the wave loads and an example is shown in Figure 1. It is assumed in the analysis that the wind and wave are perfectly aligned which is a fair assumption for deeper water further offshore projects (i.e.…”
Section: Figure 1: Loads Acting On a Typical Offshore Wind Turbine Fomentioning
confidence: 99%
“…fetch distance is high). Analysis carried out by Arany et al [6] showed that the loads from 1P and 3P are orders of magnitude lower than wind and wave but they will have highest dynamic amplifications. The effect of dynamic amplifications due to 1P and 3P will be small amplitude vibrations.…”
Section: Figure 1: Loads Acting On a Typical Offshore Wind Turbine Fomentioning
confidence: 99%
“…The loads acting on the foundation are typically one way cyclic and many of loads are also dynamic in nature. Further details of the loading can be found in Arany et al (2014). (b) It is well known from literature that repeated cyclic or dynamic loads on a soil causes a change in the properties which in turn can alter the stiffness of foundation, see Bhattacharya (2011, 2012).…”
Section: Introductionmentioning
confidence: 99%